Oprah Winfrey : global media leader - Krohn, Katherine E. (USA today lifeline biographies., 2009)
Chronicles the life and career of Oprah Winfrey from her roots as a farm girl in rural Mississippi to being the first African American woman to become a billionaire and discusses her film appearances, success as a talk-show hostess, and her humanitarian efforts in the area of child abuse.